Factors Affecting Dietary Improvements in Elderly Residents of Long-Term Care Institutions Receiving Domiciliary Dental Care - Hitomi Kikuchi (MDPI AG, 2021)
Background: Oral disabilities occur due to tooth loss. This study aimed to investigate oral and systemic factors related to diet in elderly residents receiving domiciliary dental care. Methods: The subjects were 74 consenting residents. Survey items included whether subjects could eat independently and diet type. Subjects were examined by the dentist for the number of teeth, occlusal support index, and wearing dentures. Contingency table analysis was performed to determine what levels of decline in general and oral functions led to difficulties eating a normal diet. Results: There was a significant difference in the mean number of activities of daily living (ADL) requiring assistance evident between subjects eating a normal diet and those eating fluid boiled rice (p < 0.01). A comparison of occlusal support and diet type showed that most subjects who ate a soft diet or gruel had no occlusal support. Almost all subjects who ate a normal diet wore dentures. However, only 38% of subjects eating a soft diet and 40% of those eating gruel did wear dentures; both group differences were significant (p < 0.01). Conclusions: Future studies need to further investigate oral factors related to the type of diet and their relationships to domiciliary dental care in older adults.